Pengaruh Pendidikan Kesehatan dalam Layanan Home Care Terhadap Pengetahuan dan Sikap Ibu Hamil Trimester II dan III Tentang Senam Hamil di UPTD Puskesmas Ubung Tahun 2021 - Lina Sundayani; Ni Nengah Arini Murni; Intan Gumilang Pratiwi; Ida Royani (PublisihingId, 2022)
Background: The threat of maternal death is still a major problem in developing countries, including Indonesia. One of the scopes in controlling MMR in Indonesia is to improveservices antenatal care. Health services that are home visits (Home Care) by health workers can provide education and a deeper understanding of treatment. Objective: To determine the effect of health education inservices home care on the knowledge and attitudes of pregnant women about pregnancy exercise. Method: This study was astudy quasi-experimental using the Nonequivalent Control Group Design. This research was conducted from June to July 2021. The population in this study were all pregnant women who were in the working area of ​​the UPTD Puskesmas Ubung, totaling 121 pregnant women. The sample with the number of pregnant women in the second and third trimesters who are in the working area of ​​the UPTD Puskesmas Ubung 33 pregnant women. Data analysis using Paired Samples Test and Wilcoxon Signed Rank Test. Results: The average score of knowledge of pregnant women about pregnancy exercise in the intervention group before being given health education was 67.33±13.74, while the average score of knowledge of pregnant women about pregnancy exercise after being given health education was 86.00±10.72. The results of this study indicate the effect of health education in home care services on changes in knowledge with a value (P = 0.000). The average score of pregnant women's attitudes about pregnancy exercise in the intervention group before being given health education was 57.00±18.61, while the average score of pregnant women's attitudes about pregnancy exercise after being given health education was 73.66±15.17. The results of this study indicate that there is an effect of health education in home care services on changes in attitudes with a value of (P = 0.002). Conclusion: There is an effect of health education inservices home care on the knowledge and attitudes of pregnant women trimester II and III about pregnancy exercise.